HAPİS CEZALARININ VE CEZAEVLERİNİN TARİHİ GELİŞİMİ - (:unkn) unknown (My University, 2015)
Bu çalışmada, hapis cezaları ve cezaevlerinin tarihi gelişimi incelenmiştir. Tarihi süreç incelendiğinde, cezaevleri, genellikle hükümlülerin yargılama süresince tutuldukları ya da ölüm cezasının infazına kadar bekletildikleri yerler olmuştur. Çalışmada öncelikle cezaevlerinin doğuşundan önceki süreç incelenmiş, ardından cezaevlerinin doğuşu ve gelişimi değerlendirilmiştir. Ayrıca hapis cezasının infaz sistemlerine değinilmiştir. Son olarak hapis cezalarının Türk Hukukundaki gelişimi incelenmiştir.

This study examines the historical evolution of prison sentences and prisons. Within the historical process, prisons have generally been places where convicts were held during their trials or were kept until the execution of their death sentences. The study respectively focuses on the period before the birth of prisons, the emergence of prisons and their development. The execution system of imprisonment is also examined within this work. Finally, the development of prison sentences in the Turkish Law is analyzed.
(Historical Evolution of Prison Sentences and Prisons)
Keywords: Hukuk